Inequality and poverty in Africa in an era of globalization: Looking beyond income to health and education - David E. Sahn; Stephen D. Younger (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
This paper describes changes over the past 15-20 years in non-income measures of wellbeing—education and health—in Africa. We expected to find, as we did in Latin America, that progress in the provision of public services and the focus of public spending in the social sector would contribute to declining poverty and inequality in health and education, even in an environment of stagnant or worsening levels of income poverty. Unfortunately, our results indicate that in the area of health, little progress is being made in terms of reducing pre-school age stunting, a clear manifestation of poor overall health. Likewise, our health inequality measure showed that while there were a few instances of reduced inequality along this dimension, there was, on balance, little evidence of success in improving equality of outcomes. Similar results were found in our examination of underweight women as an indicator of general current health status of adults. With regard to education, the story is somewhat more positive. However, the overall picture gives little cause for complacency or optimism that Africa has reaped, or will soon reap the potential benefits of the process of globalization. – health ; education ; wellbeing ; Africa
Keywords: I18; I28; I32; 330; Lebensqualität; Armut; Bildung; Gesundheit; Afrika; Soziale Ungleichheit